נמצא את הנגזרת לפונקציה y = e x {\displaystyle y=e^{x}} .
d ( e x ) d x = lim h → 0 e x + h − e x h = lim h → 0 e x ⋅ e h − e x h = lim h → 0 e x ( e h − 1 ) h = lim h → 0 e x ⋅ lim h → 0 e h − 1 h {\displaystyle {\frac {d(e^{x})}{dx}}=\lim _{h\to 0}{\frac {e^{x+h}-e^{x}}{h}}=\lim _{h\to 0}{\frac {e^{x}\cdot e^{h}-e^{x}}{h}}=\lim _{h\to 0}{\frac {e^{x}(e^{h}-1)}{h}}=\lim _{h\to 0}e^{x}\cdot \lim _{h\to 0}{\frac {e^{h}-1}{h}}}
אם נשוב להגדרת המספר e {\displaystyle e} , נראה כי y = e x {\displaystyle y=e^{x}} הוגדרה כפונקציה מעריכית ששיפועה 1 בנקודה ( 0 , 1 ) {\displaystyle (0,1)} .
לפיכך d ( e x ) d x = e x {\displaystyle {\frac {d(e^{x})}{dx}}=e^{x}} .